Effectiveness of Organic Chemicals as Corrosion Inhibitors in Saturated Calcium Hydroxide Solution with Reduced Alkalinity - Khurana, Rahul (My University, 2014)
Reinforced concrete is the most widely used construction material but its durability issues still exist. Apart from structural design failures, the most significant cause of deterioration and premature failure of RC structures is the corrosion of the steel reinforcement. In last quarter century, many methods have been developed to reduce or prevent corrosion of steel in concrete. From all the methods available for corrosion protection, corrosion inhibitors sound very promising. In last two decades, corrosion inhibitors have been extensively used to protect steel reinforcement in RC structures. Most of the commercially available corrosion inhibitors are used for chloride (Cl-) induced corrosion and are not effective for carbonation induced corrosion. Commercially available corrosion inhibitors being very expensive affect the total cost of structure. Due to which, there arises a need to find a cheaper replacement of these corrosion inhibitors. In this study, effectiveness in corrosion inhibition of some commonly available cheap organic chemicals is evaluated. Corrosion inhibition of Tartaric acid, Maleic acid, Adipic acid, Phthalic acid and Oxalic acid with 0.25%, 0.5% and 1% addition is assessed. Fe 500 HYSD steel bars of 12 mm diameter and 60 mm length are immersed in seven different solutions for 240 hours. Corrosion monitoring of these steel bars is performed at 1 hour, 24 hours, 48 hours, 120 hours and 240 hours of immersion. It is observed that all the chemicals are adequately effective in corrosion inhibition of steel bar at 0.5 % of addition but do not perform well with 0.25% and 1% addition. Performance of Tartaric acid and Oxalic acid is finest.
M.E. (Structural Engineering)
Keywords: Corrosion; Carbon Dioxide